Comparison of PSA Values from capillary dried blood spot analysis and venous serum samples - Lucas Engelage; Niklas Behnel; Agron Lumiani; Alexander Tamalunas; Alexander Buchner; Ronald Sroka (PLoS ONE, 2025)
Prostate-specific antigen (PSA) testing is a key tool in the early detection and monitoring of prostate cancer. While venous blood is the standard matrix for PSA measurement, capillary blood sampling represents a minimally invasive alternative that may facilitate broader access to testing. This prospective study investigated the agreement between capillary and venous measurements of total and free PSA in 224 male patients at ALTA Klinik Bielefeld, Germany. Blood samples were collected between April and June 2021 and analyzed using electrochemiluminescence immunoassays. The results showed strong correlations between capillary and venous samples for both total PSA (r = 0.99, p < 0.01) and free PSA (r = 0.98, p < 0.01). Mean differences were 0.35 ng/mL for total PSA and 0.27 ng/mL for free PSA. Bland-Altman analysis demonstrated good agreement between both methods, with most values falling within the 95% confidence limits. These findings suggest that capillary blood sampling may be a suitable alternative to venous blood for PSA testing, particularly within the clinically relevant range up to 10 ng/mL. Furthermore, the feasibility of determining both total and free PSA in capillary samples allows calculation of the fPSA/tPSA ratio, which may improve diagnostic specificity in early prostate cancer detection.